PENGARUH BINDER TERHADAP KARAKTERISTIK PEMBAKARAN BRIKET BATUBARA SUBBITUMINUS - ANAM, AHSONUL
The influence of clay and starch binder on the physical and combustion characteristic of briquette was studied. The experimental was carried out with different content of binder added to the briquette. The percentage of clay binder is varied from 5 % to 15 %, and that of starch binder, is from 3 % to 7 %. The briquette combustion was conducted in electrical tube furnace with air forced convection. The results showed that the compressive strength of briquette increases with increasing of starch and clay content. The compressive strength of the briquette is varied from 1000 to 1 600 N (starch binder) higher than 0 - 200 N for clay binder. The ignition time increases with increasing of binder, for starch briquette varied from 27 second to 52 second (T, 873 K), 91 second to 1 30 second (Tr 773 K), and for clay briquette varied from 43 second to 84 second (Tr 873 K), 202 second to 232 second (T r 773 K). The ignition temperature for starch briquette is T r 653 K, lower than that for clay briquette (fj. 673 K - TF 753 K). The influence of furnace temperature on the ignition time is more dominant than that of binder percentage. Mode of starch briqutte combustion is shrinking core and that of clay briqutte is shrinking particle. The rate of combustion decreases as percentage of binder increases for both binder.